1978
DOI: 10.1073/pnas.75.8.3640
|View full text |Cite
|
Sign up to set email alerts
|

A rationale for stabilization of oxygen-labile enzymes: application to a clostridial hydrogenase.

Abstract: ABSTRACr A general procedure for stabilization of 02-labile enzymes exploiting "salting out" of oxygen from the microenvironment in the molecular layers immediately adjacent to charged surfaces of polyionic solid adsorbents has been develope. Empirical verification of this rationale is provided. The half-life of air inactivation of the Og-labile hydrogenase (EC 1.12.7.1) from Clostridium pasteurianum is increased 20-to 2-fold simply by adsorption (noncovalent binding) in dilute Tris-HCI buffer on common anion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…An additional, highly attractive explanation for the strong inhibition of autoxidation of vesicle-bound flavins (T< T~) is the well-known "salting out" phenomenon [17]. This effect has been originally exploited for the stabilization of oxygen-labile enzymes by charged surfaces of polyionic solid adsorbents.…”
Section: Discussionmentioning
confidence: 99%
“…An additional, highly attractive explanation for the strong inhibition of autoxidation of vesicle-bound flavins (T< T~) is the well-known "salting out" phenomenon [17]. This effect has been originally exploited for the stabilization of oxygen-labile enzymes by charged surfaces of polyionic solid adsorbents.…”
Section: Discussionmentioning
confidence: 99%
“…The generation of artificial environments around the enzyme molecules has been proposed as a way to prevent inactivation. A hydrophilic environment may reduce the concentration of hydrophobic organic solvents or some gases near to the enzyme 108. A hydrophobic environment may greatly reduce the exposition of the enzyme to very hydrophilic deactivating reagents, like hydrogen peroxide 76,95…”
Section: Global Comparison Of Different Immobilization Strategiesmentioning
confidence: 99%
“…Using this strategy, it has been found that PEI can have some positive effects on enzyme stability by generating a partition of hydrophobic compounds (like organic solvents or gases like oxygen) from the enzyme environment (Figures 4 and 6). 69 In general, support preparation is not optimized to maximize the polymeric bed thickness, as just one molecule of the polymer may be enough to immobilize a protein, although this may reduce the impact of the immobilization on the enzyme properties. The fact that this support may rapidly adsorb most proteins in crude extract makes the presence of contaminants detrimental since it may reduce the final loading of the target protein.…”
Section: Use Of Supports Just Activated Peimentioning
confidence: 99%